Fast Orthogonal Row-Column Electronic Scanning With Top-Orthogonal-to-Bottom Electrode Arrays - Ceroici, Chris (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2017)
Recently, top-orthogonal-to-bottom electrode 2-D arrays were introduced as a practical design for 3-D ultrasound imaging without requiring the wiring of a 2-D grid of elements. However, previously proposed imaging schemes suffered from speed or image-quality limitations. Here, we propose a new imaging scheme which we call Fast Orthogonal Row-Column Electronic Scanning (FORCES). This new approach takes advantage of bias sensitivity to enable high-quality and fast B-scan imaging. We compare this imaging scheme with an equivalent linear array, a previously proposed row-column imaging scheme, as well as with the Explososcan imaging scheme for 2-D arrays through simulations. In a point phantom simulation, the lateral (azimuthal) resolution of a 64 ×64 element 6.67-MHz λ /2-pitch array using the FORCES imaging scheme with an f-number of 1.7 was 0.52 mm with similar in-plane image quality to an equivalent linear array but with improved and electronically steerable elevational resolution. When compared with other 3-D imaging schemes in point phantom simulations, the FORCES imaging scheme showed an azimuthal resolution improvement of 54% compared with Explososcan. Compared with a previously introduced row-column method, the FORCES imaging scheme had similar resolution but a 25-dB decrease in sidelobe amplitude, significantly impacting contrast to noise in scattering phantoms